FAST TRACK REHABILITATION IN THYROID INTERVENTIONS - V. K. Lyadov; D. R. Pashaeva; M. V. Nekludova (Опухоли головы и шеи, 2017)
Introduction. Thyroid surgeries are one of the most common surgical interventions. Duration of hospital stay depends on the risk of postoperative complications, primarily, transient or permanent hypocalcemia, recurrent laryngeal nerve paralysis, bleeding.Objective: presentation of first-hand results of using a protocol of enhanced recovery after thyroid surgery by us.Materials and Methods. In the study, results of treatment of 162 patients who underwent surgery in the period from January 2014 to January 2016 are analyzed. In 22 (13.5 %) patients the surgery was performed endoscopically using bilateral axillo-breast approach (ВАВА). Results. No deaths were registered. In 2 patients, intraoperative complications were observed: In one case the recurrent laryngeal nerve was transected in a patient with retrosternal giant (larger than 15 cm) nodular goiter; in the 2nd case, the cricoid cartilage of a female patient was damaged by a harmonic scalpel during endoscopic intervention. Mean surgery duration in the studied group was 69.5 ± 15.7 min. Postoperative complications were observed in 5 (3 %) patients: In 1 it was subcutaneous emphysema after endoscopic surgery, in 2 patients – laryngospasm, in another two – transient hypocalcemia. Mean duration of hospital stay was 2.1 ± 0.5 days.Conclusions. Based on literature data analysis and results of our study, we can conclude that the use of enhanced recovery protocols after thyroid surgeries is safe with low rate of complications and earlier hospital discharge.